2019
DOI: 10.3390/bs9100102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Rejection Letters on Applicants’ Reactions

Abstract: Organisations appear to pay little attention to rejection letters, considered a special form of organisational communication, despite a growing body of literature that shows they play an important role in terms of employer branding. This study aims to empirically test how applicants’ perceptions are affected by differently manipulated rejection letters. In detail, a sample of 138 rejected candidates filled in an ad hoc questionnaire on perceived selection procedure fairness and satisfaction, after receiving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…Earlier research has documented similar behavior [17]. Rapid feedback increases the likelihood of future applications [5] and female applicants are less likely to apply again after being rejected [4].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Earlier research has documented similar behavior [17]. Rapid feedback increases the likelihood of future applications [5] and female applicants are less likely to apply again after being rejected [4].…”
Section: Introductionmentioning
confidence: 60%
“…Only 14 of the 74 responses can be categorized as neutral or indifferent. 5 Of the 60 respondents who expressed negative feelings, 13 used the word "frustrated" or "frustrating", and 9 used the word "disappointed" or "disappointing". Examples of the responses expressing negative feelings are shown below.…”
Section: Frustration With Current Practicesmentioning
confidence: 99%
“…Though it may be tempting to employ a letter template to reject a submission, Cortini et al [9] have shown that customizing a rejection letter affects the perception of fairness and intention to re-apply. Editors may customize a letter by addressing the recipient formally using the author's name and title ("Dear Professor Smith, " not "Dear Lisa, "); including the title of the submission; offering some lines of sincere praise for worthy aspects of the paper; and providing a gentle explanation as to why the manuscript is not suitable at this time.…”
Section: Customization Explication and Praisementioning
confidence: 99%
“…El uso de una rúbrica de evaluación, pruebas estandarizadas y un proceso de entrevistas que pueda ser realizado por al menos un miembro independiente de la organización pueden aumentar la percepción de justicia del futuro trabajador. Desde el punto de vista comunicativo, se debe explicar al aspirante cómo funciona el proceso de selección y cuál es el perfil esperado para el candidato a ocupar la posición vacante (Giannantonio Cristina, 2019; Konradt et al, 2015;McCarthy et al, 2017), estas explicaciones se ha visto que aumentan la percepción de justicia procedimental (Melchers & Körner, 2019), sin embargo, en la literatura científica se expresa que aún falta investigación sobre los mensajes, el contenido y las consecuencias de presentar esta información a las personas interesadas en un cargo (Cortini, Galanti, & Barattucci, 2019).…”
Section: Proceso De Selección De Personalunclassified